2016
DOI: 10.1002/jcb.25613
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenesis and Diabetic Erectile Dysfunction: How Relevant Is Glycemic Control?

Abstract: Erectile dysfunction (ED) is a complication of diabetes, condition responsible for causing endothelial dysfunction (EDys) and hampering repair mechanisms. However, scarce information is available linking vasculogenesis mediated by Endothelial Progenitor Cells (EPCs) and diabetes-associated ED. Furthermore, it remains to be elucidated if glycemic control plays a role on EPCs functions, EPCs modulators, and penile vascular health. We evaluated the effects of diabetes and insulin therapy on bone marrow (BM) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…In this regard, recent data have suggested that SDF-1α was upregulated by DPP-4 inhibition and has protective roles in progressive DN ( Takashima et al, 2016 ). Previous studies have reported that SDF-1α levels were significantly reduced in both STZ-induced diabetic mice ( Gallagher et al, 2007 ; Li et al, 2012 ) and diabetic patients ( Angela Castela et al, 2017 ) compared to the normal groups, while it was markedly increased in the DPP-4 inhibitor treatment group ( Fadini et al, 2010 ; Fujita et al, 2014b ; Lovshin et al, 2017 ). In parallel with SDF-1α upregulation, DPP-4 inhibitor treatment clearly attenuated the progression of albuminuria not only in animal experiments ( Nistala et al, 2014 ) but also in clinical studies ( Fujita et al, 2014b ).…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, recent data have suggested that SDF-1α was upregulated by DPP-4 inhibition and has protective roles in progressive DN ( Takashima et al, 2016 ). Previous studies have reported that SDF-1α levels were significantly reduced in both STZ-induced diabetic mice ( Gallagher et al, 2007 ; Li et al, 2012 ) and diabetic patients ( Angela Castela et al, 2017 ) compared to the normal groups, while it was markedly increased in the DPP-4 inhibitor treatment group ( Fadini et al, 2010 ; Fujita et al, 2014b ; Lovshin et al, 2017 ). In parallel with SDF-1α upregulation, DPP-4 inhibitor treatment clearly attenuated the progression of albuminuria not only in animal experiments ( Nistala et al, 2014 ) but also in clinical studies ( Fujita et al, 2014b ).…”
Section: Discussionmentioning
confidence: 90%
“…8 Furthermore, in diabetic patients, independently from age, ED is usually more severe than in non-diabetics 9 and their glycemic control is independently associated with the risk of ED. 10,11 Recent guidelines on male sexual dysfunction recommend the assessment of hormonal status in the diagnostic flow-chart of ED. The reason is that hormones impairment is strictly involved in sexual function.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular endothelium, a simple squamous epithelial layer on the surface of blood vessels, plays a major role in endocrine signaling and has a wide variety of biological functions (7,8), including the process of penile erection (9). Endothelial dysfunction, caused by harmful changes due to high glucose levels and increased oxidative stress in endothelial cells, is critical for the progression of DED (10). In addition to direct damage to endothelial cells, diabetes may hinder the angiogenesis implicated in vascular repair mechanisms, further affecting vasodilation and cavernous blood perfusion, which are essential for normal erectile function.…”
Section: Introductionmentioning
confidence: 99%